Preliminary Study of Jatropha Curcas Oil as Ester-Based Drilling Fluids - Sonny Irawan, Sonny; Kania Dina, Kania (2010)
It had been considered that oil-based mud (OBM) had toxic substances. Various types of low toxicity oils had been introduced to replace the more toxic mineral or OBM system. Jatropha curcas oil which is made from renewable sources consists of the simple alkyl esters of fatty acids might be an alternative resource to replace conventional OBM. In this preliminary study, Jatropha curcas oil was converted to ester form and mixed with drilling mud additives until all the ingredient form a stable emulsion. Thermal conditioning of the mud at 250°F for 16 hours indicated negligible changes in chemical composition of the mud. Having similar physical properties with palm oil methyl ester and diesel oil for OBM, Jatropha FAME is expected to have acceptable performance in drilling fluid formulation.